2012
DOI: 10.3109/00365521.2012.667146
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal cytokine gene expression profiles as biomarkers of response to infliximab in ulcerative colitis

Abstract: High expression of Th1- and Th17-related cytokines in the mucosa of UC patients can potentially predict a favorable outcome of IFX induction therapy. Th2 and Treg-related mediators do not appear useful as predictive markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…4E). Addition of infliximab to cell cultures did not increase the level of soluble IL-2R (of which CD25 is a subunit) levels during the 7 days of cell culture (day 1; 34 (18-53) versus 22 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) + T were detectable at day one (Fig. 4 H).…”
Section: Infliximab Reduces Proliferation and Expression Of Cd25 In Tmentioning
confidence: 96%
“…4E). Addition of infliximab to cell cultures did not increase the level of soluble IL-2R (of which CD25 is a subunit) levels during the 7 days of cell culture (day 1; 34 (18-53) versus 22 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) + T were detectable at day one (Fig. 4 H).…”
Section: Infliximab Reduces Proliferation and Expression Of Cd25 In Tmentioning
confidence: 96%
“…In previous studies, mucosal TNF-a gene expression was identified as a marker of the response to therapy or long-term outcome and clinical relapse [17,28]. Other studies demonstrated that high pre-treatment mucosal interleukin-17A and interferon-c gene expression levels result in an increased likelihood of clinical and endoscopic remission after IFX therapy in patients with UC [29]. We observed that expression of PRKCDBP and TNF-a in colonic mucosa post-IFX treatment was significantly lower in endoscopic responders than in non-responders.…”
Section: Clinical Outcomes In the First Year According To Prkcdbp Expmentioning
confidence: 96%
“…Because a subset of patients with UC clearly do not respond to IFX, it is important to identify predictors of a response to this rather expensive and potentially harmful drug to allow selection of appropriate patients [30,31]. However, few studies of the ability of mucosal biomarkers to predict the clinical course of IBD or the response to therapy are available [16,17,28,29,32]. Moreover, few validations have been performed, and mucosal biomarkers play a minor role, if any, in clinical practice.…”
Section: Clinical Outcomes In the First Year According To Prkcdbp Expmentioning
confidence: 97%
“…4,5 It has also been assumed that alterations of the mucosal cytokine profile may be an important action of infliximab for UC. Rismo et al 8 reported that high expression of Th1-and Th17-related cytokines in the mucosa of UC patients were predictive of a favorable outcome of infliximab induction therapy. However, changes in various circulating cytokine profiles prior to and after infliximab treatment have not been extensively examined.…”
Section: Introductionmentioning
confidence: 99%